Shape of things to come : new sculpture - Holborn, Mark; Saatchi Gallery (London : Jonathan Cape, 2009)
Focuses on contemporary sculpture. This book presents objects which are derived from various conceivable materials and vary from abstract arrangements to re-configurations of everyday forms in magnificent transformations of the mundane, such as giant electric sockets, to the recurring theme of the human body.
boek